Atrial fibrillation as a risk factor of severe course of COVID-19. (14th October 2021) - Mielczarek, A; Kasprzak, J D; Plewka, M
Abstract: Background: Coronavirus disease (COVID-19), the pandemic caused by severe acute respiratory syndrome coronavirus, influences on morbidity and mortality and results in changes of human life. It seems that comorbidities play a vital role in severe course of COVID- 19. Nevertheless, how chronic diseases affect respiratory failure is poorly validated. Purpose: Our aim was to compare the severity of the course of COVID-19 and the prognosis in patient with and without atrial fibrillation (AF). Methods: We analyzed 199 patients (72 female, mean age 67±13 years) with COVID-19 hospitalized in our Department since November 2020, including, 68 patients with AF (28 female, mean age 74.5±8 years). Although, only 45 patients took anticoagulants before, the treatment was initiated to all patients with AF on admission to the hospital. Patients with AF were characterized by lower left ventricle ejection fraction than those without AF (49% vs. 54%, p=0.0007). Results: The severe course of COVID, defined as saturation below 90%, lung involvement above 50% in computer tomography, the need for high- flow oxygen therapy, was noticed in 98 patients (36 pts with AF, 32 pts without AF, p=0.27). Moreover, there was no difference between the groups among separately the need for high- flow oxygen therapy, saturation below 90% and lung involvement above 50% in computer tomography. The absence of atrial fibrillation, with a significance of p=0.01, predisposes to a better prognosis based on the patient's discharge. In multivariate analysis, the factors suggesting a poor prognosis, defined as death or transfer to Intensive Care Unit, were severe course of COVID (p=0.01) and the need for high- flow oxygen therapy (p=0.042). Conclusions: It is noticed that the presence of AF is associated with a poor prognosis in COVID. Further analysis is still needed to prove this statement. Funding Acknowledgement: Type of funding sources: None.